Asynchronous Web Services Using WS-Addressing developing asynchronous web applications using callback services. - Kodali, Raghu
Today's IT organizations have tens of applications and services that perform some well-defined tasks such as inventory, billing, expense reporting, and order entry. With the evolution of internet and e-business, enterprises have started to think about how different applications in a disconnected mode can work independently but at the same time be a part of an information workflow process.